Modeling of Microwave Drying of Fruits. Part II: Effect of Osmotic Pretreatment on the Microwave Dehydration Process - Arballo, Javier Ramiro (2012)
The heat and mass transfer during the combined process of osmotic–microwave drying (OD-MWD) of fruits was studied theoretically and experimentally through modeling and numerical simulation. With the aim of describing the transport phenomena involved in the combined dehydration process, the mass and energy microscopic balances were set out. For the first step (OD), two models with different levels of complexity were proposed, an osmotic–diffusive and a countercurrent flow diffusive model. For MWD, the energy and mass balances were solved, using moisture- and temperature-dependent properties; inner heat generation due to transformation of the electromagnetic energy was accounted for by using the approximation of Lambert's law. The numerical solution obtained from OD was incorporated as initial values for the simulation of MWD. The model validation was satisfactorily carried out in pears, both fresh and osmodehydrated for 2 h in sucrose solutions and then irradiated in a microwave oven at 500 W. From the results it was observed that a higher dehydration rate was reached during microwave drying when the fruits were pretreated with 40 and 60°Brix sucrose solution.